Razlike med trenerji in tekmovalci o znanju in odnosu do dopinga v slovenskem judu - Mardjonović, Brigita (Šport (Ljubljana), 2020)
The survey involved 91 judo competitors and coaches (57 men and 34 women) from Slovenia. It included competitors from the three eldest age groups: Cadets, Juniors, and Seniors. To collect the data, examinees were required to complete the survey questionnaire and another questionnaire on their Knowledge on Doping (KD). Statistically significant differences between coaches and competitors were found in the opinion on doping in judo. Significantly more coaches thought that doping was present in judo. Confidence in the coach and the nutritionist also showed differences. In the confidence to seek nutritional supplement advice, logically, several competitors responded with a "coach", as all respondents received the same questionnaire. Knowledge about doping and nutritional supplements has been reported by many coaches through education. The difference in the knowledge gained from the coach, for the benefit of the competitors and the competitors, was again detected due to the aforementioned same questionnaire for both the competitors and the coaches. None of the coaches indicated that they had no knowledge. This was not the case for competitors, which proved to be a statistically significant difference. The findings of the research will thus in particular encourage and contribute to the further, improved, education and awareness of doping among Slovenian competitors and coaches in judo.
Keywords: attitude towads doping; coaches; competitors; doping; judo; knowledge on doping; odnos do dopinga; Slovenia; Slovenija; šport; tekmovalci; trenerji; znanje o dopingu